Milling of Ti alloy honeycomb treated by ice fixation in cryogenic. Issue 6 (2nd November 2018) - Fengbiao, Wang; Wang, Yongqing; Wang, Jianson; Zhang, Jiayi
ABSTRACT: This article presents the first comprehensive investigation on ice fixation milling method for titanium (Ti) alloy honeycomb with cryogenic cooling. Milling simulation model of ice fixation was established, the material was treated by ice fixation process, and a series of cryogenic experiments was conducted by CNC milling machine. The honeycomb properties and reasons of machining defects were analyzed in details, whilst cryogenic milling mechanism with ice fixation was deduced. The analysis indicated that compared to the conventional processing way, the ice fixation milling surfaces have great improvement, and the processing defects such as burr, collapse edge are effectively suppressed, as well as ice fixation cryogenic method can improve the strength of honeycomb. Meanwhile, the cutting depth has greater influence on surface quality. Furthermore, the influence order of cutting parameters on the milling force: cut deep is the largest and more than three times can be improved, followed by feed speed, and the spindle speed has minimal impact. Conclusion: for efficient processing of Ti alloy honeycomb material with small in-plane radial equivalent strength and low rigidity thin-wall, the ice fixation provides a new processing method with cryogenic cooling.